A Breakdown in Metabolic Reprogramming Causes Microglia Dysfunction in Alzheimer's Disease - Baik, Sung Hoon; Kang, Seokjo; Lee, Woochan; Choi, Hayoung; Chung, Sunwoo; Kim, Jong-Il; Mook-Jung, Inhee (Cell metabolism, 2019)
Reactive microglia are a major pathological feature of Alzheimer's disease (AD). However, the exact role of microglia in AD pathogenesis is still unclear. Here, using metabolic profiling, we found that exposure to amyloid-β triggers acute microglial inflammation accompanied by metabolic reprogramming from oxidative phosphorylation to glycolysis. It was dependent on the mTOR-HIF-1α pathway. However, once activated, microglia reached a chronic tolerant phase as a result of broad defects in energy metabolisms and subsequently diminished immune responses, including cytokine secretion and phagocytosis. Using genome-wide RNA sequencing and multiphoton microscopy techniques, we further identified metabolically defective microglia in 5XFAD mice, an AD mouse model. Finally, we showed that metabolic boosting with recombinant interferon-γ treatment reversed the defective glycolytic metabolism and inflammatory functions of microglia, thereby mitigating the AD pathology of 5XFAD mice. Collectively, metabolic reprogramming is crucial for microglial functions in AD, and modulating metabolism might be a new therapeutic strategy for AD. [Display omitted] •Aβ induces metabolic reprogramming of microglia from OXPHOS to glycolysis•Metabolic reprogramming of microglia is dependent on the mTOR-HIF-1α pathway•Chronic exposure to Aβ induces metabolic defects of microglia•Metabolic boosting with IFN-γ restores immunological function of microglia Baik et al. report that amyloid-β acutely triggers microglial activation and metabolic reprogramming from OXPHOS to glycolysis. However, chronic exposure to amyloid-β induces overall metabolic defects in microglia in a model of Alzheimer's disease. Treatment with IFN-γ restores glycolytic metabolism and immunological function of microglia, suggesting that modulation of microglial metabolism may be a potential therapeutic strategy.